Peran Kepala Sekolah dalam Menciptakan Budaya Disiplin Guru di Lingkungan Sekolah (Studi Kasus di SMPN 3 Pangarengan) - Siti Farida; Lutfiyati Lutfiyati (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2026)
Abstract Teacher discipline culture is a pattern of values, norms, and behaviors that reflects work discipline as an integral part of school culture. This condition includes punctuality, teaching preparedness, and compliance with school regulations. Based on this background, this study addresses two research problems: First, how does the principal implement the principles of educational management in creating a culture of teacher discipline at SMPN 3 Pangarengan? Second, what are the implications of the principal's role in creating a culture of teacher discipline for the institution? This study employed a qualitative approach with a descriptive research design. The data were collected through observation, interviews, and documentation. The informants consisted of the principal, teachers, and students. The results of the study indicate that: First, the implementation of educational management principles in creating a culture of teacher discipline at SMPN 3 Pangarengan has been carried out effectively through the functions of educational management, namely planning, organizing, directing, and evaluation. At the planning stage, the principal identified problems related to teacher discipline and formulated appropriate policies. At the organizing stage, the principal delegated duties and responsibilities to the vice principal, teacher-on-duty, and teachers. At the directing stage, the principal provided guidance, coaching, motivation, and exemplary leadership in implementing discipline. At the evaluation stage, the principal monitored teacher attendance, conducted evaluations, and provided guidance to teachers who had not yet demonstrated disciplined behavior. Second, the principal's role in creating a culture of teacher discipline has had positive implications for the institution, including improved teacher discipline and the creation of a more orderly and conducive school environment. Keywords: Principal's Role, Teacher Discipline Culture, Teacher Discipline, Educational Management.